RANCANGAN TERAPI MUSIK SEBAGAI TERAPI NYERI LUKA PERINEUM PADA IBU NIFAS DI PMB MURTINAWITA KOTA PEKANBARU TAHUN 2023 - Octa Dwienda Ristica; Rita Afni (JOMIS (Journal of Midwifery Science), 2025)
Perineal rupture is defined as a tear that occurs when the baby is born, either spontaneously or with an instrument or action (1). In 2017 in Indonesia, 75% of mothers who gave birth vaginally experienced perineal tears/perineal rupture. It was found that of a total of 1951 mothers who gave birth spontaneously vaginally, 57% of mothers received perineal stitches, namely 28% due to episiotomy and 29% due to spontaneous tearing (2). Every mother who undergoes labor and experiences perineal rupture will feel pain, and one effort to reduce pain in perineal wounds is by providing classical music. Music can help someone become more relaxed, reduce stress, create a sense of security and prosperity, relieve sadness, make them happy, and help and relieve pain. PMB Murtinawita is one of the midwife clinics that provides care during the postpartum period. From the results of observations, around 50% of deliveries were carried out by episiotomy and 30% rupture occurred due to spontaneous tearing. The aim of this research is to create a music therapy design for perineal wound pain in postpartum mothers at the Murtinawita Independent Midwife Practice in 2023. This research design uses research and development (R&D), which is a research method used to produce certain products and test the effectiveness of certain products. The population in this study was 28 postpartum mothers with perineal wounds at the Independent Midwife Murtinawita Pekanbaru Practice. Data analysis in this research is univariate analysis.Data statistics show that the interpretation of all components is 100% good/satisfactory. From the Attractiveness, Stimulation and Dependability components, the value is very good/extraordinary, this is because the music therapy used in this study is relaxation music, where relaxation music is music with various artistic styles that plays slowly. like natural sounds that create relaxation and optimism. So it can be concluded that the music therapy carried out brought positive results for postpartum mothers with perineal wound pain. It is hoped that this music therapy design can be given to postpartum mothers with perineal wound pain so that it can help reduce pain in perineal wounds.